(untitled) (Journal of the College of Basic Education, 2022)
The research aims to study the needs of ministries’ libraries for specialized human resources in the field of information and libraries. The sample is (95) employees within the cadres of each of the ministries (Justice, Oil, Higher Education and Scientific Research, Agriculture, Construction and Housing, Immigration and Displacement, Foreign Affairs, Science and Technology, Environment, Water Resources).